2018
DOI: 10.35117/a_eng_18_03_01
|View full text |Cite
|
Sign up to set email alerts
|

Railway border crossings on Polish-Czech borderland. Level of utilization and public transport offer

Abstract: Polish-Czech borderland shows similar potential for development of railway transport. Demographic, economic and tourist potentials can cause positive effects for local and regional railways. Significant elements creating international cooperation and flow of habitants are international railway connections, especially local and regional and public transport offer. Important feature is aspiration for high level of utilization border crossings. In paper author raised issues linked with permeability of border and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Uszkai (2015) who analysed the current and historical relations along several Central European bordersections. More recent studies about cross-border passenger rail transport have confirmed an improving tendency about connectivity over the past 25 years at the Polish-Czech Intra Schengen borderland (Smolarski, 2018).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Uszkai (2015) who analysed the current and historical relations along several Central European bordersections. More recent studies about cross-border passenger rail transport have confirmed an improving tendency about connectivity over the past 25 years at the Polish-Czech Intra Schengen borderland (Smolarski, 2018).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Continuous process of unification and integration of the railway markets of the European Union countries, both in terms of legal requirements and the application of similar organizational and technical solutions, makes railway cross-border transport a significant and constantly growing share in this market [7][8][9][10]. Poland is an example of a country where this type of railway traffic (in the area of passenger and freight transport) is systematically becoming an increasingly important area of activity of railway undertakings and infrastructure managers [11][12][13][14][15]. The biggest area of activity of freight railway undertakings in this regard is to conduct border transport processes.…”
Section: Introductionmentioning
confidence: 99%